FIGURE 2 in A new species and new records of Lecanora (Lecanoraceae, lichenized Ascomycota) with usnic acid from the Antarctic region - Rosa, Iris Nadia De La; Passo, Alfredo; Rodríguez, Juan Manuel; Chiapella, Jorge Oscar; Messuti, María Inés (Zenodo, 2016)
FIGURE 2. Lecanora flavocrassa de la Rosa & Messuti sp. nov. (holotype BCRU 5388). A. habitus. B. detail of ascus apex Lecanoratype. C. ascospores. Scales: A = 1 mm; B, C = 10 μm. Published as part of Rosa, Iris Nadia De La, Passo, Alfredo, Rodríguez, Juan Manuel, Chiapella, Jorge Oscar & Messuti, María Inés, 2016, A new species and new records of Lecanora (Lecanoraceae, lichenized Ascomycota) with usnic acid from the Antarctic region, pp. 185-193 in Phytotaxa 261 (2) on page 188, DOI:10.11646/phytotaxa.261.2.8, http://zenodo.org/record/13672160